CONCEPTUALIZATION OF ARTIFICIAL INTELLIGENCE IN RUSSIAN MEDIA DISCOURSE - Elena N. Galichkina (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie)
The article focuses on the tendencies in artificial intelligence (AI) conceptualization based on the analysis of Russian media discourse. The conceptual, figurative and axiological features of AI as an abstract mental formation are identified. The conceptualization of artificial intelligence is shown to be represented in two directions: the ability of an artificial system to perform tasks that mimic human cognitive abilities and the science of modelling computerized intellectual behavior. The nuclear features of the concept with the key representation in the word combination artificial intelligence are recorded in lexicographic sources and special-purpose dictionaries; they constitute the basis for the conceptualization of artificial intelligence in media discourse. In the figurative-andperceptual aspect, artificial intelligence is conceptualized as a living being endowed with physical characteristics and analytical abilities. Artificial intelligence is noted to be conceptualized in media discourse as an object of use, development, implementation, training, that performs a wide range of vital functions, and as a subject that demonstrates anthropomorphic characteristics (the ability to memorize, explain, analyze, etc.). The conceptualization of artificial intelligence in the value dimension manifests itself through positive assessment or possible harm. The utilitarian properties are evaluated positively, whereas the hypothetical impact on humans, in the case of uncontrolled headway in this area, is assessed negatively.